REVIEW – DIGITAL TECHNOLOGIES IN DENTAL IMPLANT PLANNING - Chikh Al Sagha Sama; Cristea Ioana; Curelariu Nura; Agop-Forna Doriana; Davidescu Alexandra; Norina Forna (Romanian Journal of Medical and Dental Education)
Dental implants have become the preferred treatment method for replacing missing teeth. The success of implant therapies depends on the precision of implant placement to effectively support prosthetic outcomes that optimize form and function. With the evolution of static surgical guides over the past decades, implant placement protocols have made significant strides in ensuring precise placement. Emerging digital technologies show the potential for real-time dynamic clinical guidance during implant placement, and robot-assisted dental implant placement is a new form of dynamic surgical guidance that, in addition to visual navigation, provides guidance for implant treatment planning, osteotomy preparation, and implant placement.